2010
DOI: 10.1093/eurjhf/hfq014
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of functional mitral regurgitation according to the severity of the underlying chronic heart failure: a long‐term outcome study

Abstract: AimsTo examine the independent prognostic role of functional mitral regurgitation (FMR) and its impact across the severity of chronic heart failure (CHF) in a large population of outpatients with systolic CHF followed at two multidisciplinary clinics. Methods and resultsEchocardiography was performed upon enrolment in 469 CHF patients. Follow-up for death and heart transplant was updated on January 2007. Five-year transplant-free survival was 82.7% in patients with no or Grade I FMR, 64.4% in Grade II, 58.5% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
3
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 32 publications
8
111
3
6
Order By: Relevance
“…Recognition of the presence and severity of mitral regurgitation, especially a moderate/severe degree of mitral regurgitation, can be of great value for risk stratification, treatment decisions and prognosis prediction (2,3,21). Our studies have revealed that the indexed LVESD, LAESD, and MAA min are positively correlated with increasing grades of mitral regurgitation grading, and in particular, the indexed LVESD is sufficiently sensitive to detect moderate/severe mitral regurgitation.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Recognition of the presence and severity of mitral regurgitation, especially a moderate/severe degree of mitral regurgitation, can be of great value for risk stratification, treatment decisions and prognosis prediction (2,3,21). Our studies have revealed that the indexed LVESD, LAESD, and MAA min are positively correlated with increasing grades of mitral regurgitation grading, and in particular, the indexed LVESD is sufficiently sensitive to detect moderate/severe mitral regurgitation.…”
Section: Discussionmentioning
confidence: 62%
“…In DCM patients, chamber dilatation and alteration in the geometric relationship of the mitral valve apparatus may lead to mitral regurgitation, particularly MAA dilatation. According to previous studies (2,3,21), the presence of mitral regurgitation is associated with a poor outcome, and a moderate/severe degree of mitral regurgitation remains an independent predictor for sudden cardiac death, heart failure, and mortality in DCM patients. Surgical correction for severe mitral regurgitation can improve patients' symptoms and quality of life, reduce hospital mortality, and reveal reverse LV remodeling (14,22).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Its severity in the general HF population correlates with adverse ventricular remodeling and outcomes. Bursi et al 26 showed that reduction of mitral regurgitation after CRT correlated with an improvement in survival. In contrast, a deterioration in mitral regurgitation correlated with poorer survival.…”
Section: Post-crt: Programming and Monitoringmentioning
confidence: 99%
“…Mit zunehmender New York Heart Association (NYHA)-Klasse und Schweregrad der Mitralklappeninsuffizienz steigt die Mortalität an [8,9]. Da derzeit nur die medikamentöse Therapie der Herzinsuffizienz (insbesondere mittels ACE-Hemmern) bei funktioneller Mitralklappeninsuffizienz eine medikamentöse Option bietet, stellt die operative Therapie den Goldstandard der Behandlung der schweren Mitralklappeninsuffizienz dar, zumal diese die Mortalität senkt [10][11][12].…”
Section: Die Nachsorge Von Patienten Nach Mitraclip ® -Implantationunclassified